EFEKTIVITAS MEDIA APRON STORIES UNTUK MENINGKATKAN KETRAMPILAN BICARA ANAK - Wardani, Fitria Esti; Purwati, Purwati; Sugiyadi, Sugiyadi (Universitas Muhammadiyah Magelang, 2015)
This study aims to determine the effectiveness of Media Apron Stories to improve speaking skills of children. Study Design This is a Class Action Research (PTK) with three cycles, each cycle consisting of four phases, each of which includes action planning, action, observation and reflection. Methods of data collection in this study is a test and an interview. The instrument used was the assessment sheet. Test the validity of this research is done using expert opinion (professional judgment) in the field of early childhood education, especially with regard to children’s ability to speak with a grating instruments which have been created by experts (exspert judgment).The results of this study can be seen that the ability to speak has been improved with media Apron story. In the first cycle, the ability to speak all subjects began to grow by a percentage derived by all subjects by 25%. In the second cycle, the ability to speak increased the percentage of subjects I amounted to 70.83%, subject II amounted to 62.50%, and 62.50% of the subjects III. In the third cycle, the ability to speak increased from Cycle II with the percentage of subjects I amounted to 83.33%, subject II 75.00%, and 75.00% subjects III. Based on these percentages can be concluded that the Media Apron Stories Effective to improve speaking skills of children at play groups Aisyiyah Mungkid Melati Putih subdistrict of Magelang regency Academic Year 2015/2016.